1975
DOI: 10.1007/bf02010441
|View full text |Cite
|
Sign up to set email alerts
|

Microbial film development in a trickling filter

Abstract: The transmission and scanning electron microscopes were employed to visualize the sequence of the biofilm development in the trickling wastewater filter. After the deposit of a small amount of debris upon a hard surface, the bacterial cells attach and develop the matrix on which the biofilm is formed. Protozoa invade the basic layer where they feed on the bacteria. The algae are seeded upon the bacterial matrix and grow so profusely that the bacteria must develop aerial colonies in the competition for food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…1A). Mack and Anderson [58] reported that, after the establishment of the EPS matrix, algae cells begin to rapidly grow in the upper layers ( Fig. 1B and C) of the matrix causing bacteria to form aerial colonies (away from the substrate) to compete for nutrients.…”
Section: Species and Succession Of Photosynthetic Biofilmsmentioning
confidence: 97%
See 2 more Smart Citations
“…1A). Mack and Anderson [58] reported that, after the establishment of the EPS matrix, algae cells begin to rapidly grow in the upper layers ( Fig. 1B and C) of the matrix causing bacteria to form aerial colonies (away from the substrate) to compete for nutrients.…”
Section: Species and Succession Of Photosynthetic Biofilmsmentioning
confidence: 97%
“…Generally, the first inhabitors of algal biofilms are bacteria that begin to form an EPS matrix while cells begin to grow away from the growth surface [56,58]. After this conditioning has occurred algae cells are recruited to the matrix and grow in symbiosis and in competition with the bacterial cells present [55,58].…”
Section: Biotic Factors On Biofilm Development and Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…The techniques so far used for measuring variable biofilm thickness are light microscopy (Bryers and Characklis 1981;Trulear and Characklis 1982;Robinson et al 1984;Zahid and Ganczarczyk 1990;Gjaltema et al 1994), scanning (Mack et al 1975;Eighmy et al 1983;Robinson et al 1984;LeChevallier et al 1987;Switzenbaum and Eimstad 1987;Capdeville and Nguyen 1990) and transmission (Mack et al 1975;Robinson et al 1984;Christensen et al 1988;Drury et al 1993;Murga et al 1995) electron microscopy, atomic force microscopy (Bremer et al 1992;Razatos et al 1998), confocal scanning laser microscopy (Lawrence et al 1991;Lappin-Scott et al 1992;de Beer et al 1994a, b), and Fourier transform infrared spectroscopy (de Beer et al 1994b). The thickness of biofilm can be measured by image analysis software.…”
Section: Introductionmentioning
confidence: 97%
“…soil, rocks, membranes) results in permeability reduction and clogging [11]. The pore clogging of porous media by biofilms is known as "bioclogging" [8,12,13]. Although there are numerous cases where bioclogging has detrimental consequences, such as progressive plugging of water wells, ponds and trenches used for artificial aquifer recharge [14], or wetland wastewater treatment [15][16][17], there are several instances where bacteria and bioclogging may be used to advantage.…”
Section: Introductionmentioning
confidence: 99%